Examination of the influence of conjugated linoleic acid in broiler nutrition on the economic efficiency of fattening. Issue 1 (October 2021) - Brankovic Lazic, I; Markovic, R; Baltic, B; Raseta, M; Baltic, T; Djordjevic, V; Katanic, N
Abstract: The aim of this study was to examine the influence of the use of CLA (2%), from days 1, 11 or 22 of fattening, on selected production results (broiler weight after each fattening phase including at the end of fattening, viability, average daily gain and feed conversion) on the efficiency of fattening during the whole fattening period (42 days). The obtained production results were used to calculate the European production efficiency factor (EPEF) and the European broiler index (EBI) values for each fattening phase as well as for the whole fattening. The results obtained indicate that, in the later stages of fattening, the use of CLA during the whole fattening period is economically more justified than the non-CLA diets used for control broilers. With the use of CLA throughout the whole fattening, the EPEF and EBI values are consistent with these values calculated for the Cobb 500 standard. In addition to economic justification, the use of CLA also has human nutritional significance, since the broiler meat is enriched with CLA and has a more favourable n-6/n-3 fatty acid ratio.